2019
DOI: 10.1016/j.mambio.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of populations of the Pampean grassland mouse, Akodon azarae, in an agroecosystem under intensive management

Abstract: Agroecosystems in central Argentina are a good example of landscape modification by human activities. We used the Pampean grassland mouse (Akodon azarae) as a biological model to assess the effects of landscape fragmentation on the genetic structure of natural populations present in the region. The species is a habitat specialist that is numerically dominant in relatively stable environments, such as remnant areas of native vegetation, stream borders, roadsides and railway banks. We used seven microsatellite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Depending on the landscape characteristics and the land management of each agro-ecosystem, dispersal and later reproduction can be notably affected [ 10 , 11 , 12 ]. There have been several population genetics studies on patch-dependent species aiming to better understand how agricultural landscapes determine gene flow [ 13 , 14 , 15 ]. They have shown that landscape features can both restrict and facilitate the movement of individuals in natural populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the landscape characteristics and the land management of each agro-ecosystem, dispersal and later reproduction can be notably affected [ 10 , 11 , 12 ]. There have been several population genetics studies on patch-dependent species aiming to better understand how agricultural landscapes determine gene flow [ 13 , 14 , 15 ]. They have shown that landscape features can both restrict and facilitate the movement of individuals in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the population connectivity of rodents in agriculture ecosystems is thus of considerable value. Several genetic studies have highlighted that dispersal is often restricted in rodent species inhabiting agro-ecosystems because of agriculture intensification and the resulting reduction in natural habitats [ 13 , 14 , 15 , 21 ]. Maintaining and increasing landscape complexity benefits multiple species at the same time by providing many different ecological niches [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The agroecosystems of central Argentina present a remarkable spatiotemporal variability due to yearly land-use activities (i.e., harvest and plow activities) ( Fraschina et al 2012 ; Serafini et al 2019 ). Therefore, they offer a particularly interesting scenario to explore the spatial and temporal distributions of wild animal genotypes in human-modified landscapes ( Chiappero et al 2016 ; Vera et al 2019 ). Argentinean agroecosystems consist of monocultures of a few crops (corn, soybean, sunflower, and wheat) surrounded by a network of roadsides, fence lines, railways, and other border habitats that keep remnants of native flora and many introduced weeds.…”
mentioning
confidence: 99%